Tabish Khair : Critical Perspectives. - Gámez-Fernández, Cristina M. (Cambridge Scholars Publishing, 2014)
This volume approaches Tabish Khair's writings (both his theoretical proposals and his novels) from numerous different perspectives. Contributors engage from varied critical stances with Khair's academic writings in a fruitful dialogue, analyze his social, political and religious concerns, and elucidate his characteristics as a novelist and his literary powers. Furthermore, this volume is highly enriched by the presence of a hitherto unpublished play by Khair, entitled The One Percent Agency ...